\( 1 \leftarrow \quad \) For \( f(x)=9 x-6 \) and \( g(x)=\frac{x+6}{9} \), find the following functions. a. \( (f \circ g)(x) ; \) b. \( (g \circ f)(x) ; \) c. \( (f \circ g)(5) ; \) d. \( (g \circ f)(5) \) a. \( (f \circ g)(x)=x \) (Simplify your answer.) b. \( (g \circ f)(x)=\square \) (Simplify your answer.)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To tackle this fun math quest, let’s dive right in! For \( (f \circ g)(x) \), you've already noted that it's \( x \). Awesome! Now, moving on to... For \( (g \circ f)(x) \): We need to compute \( g(f(x)) = g(9x - 6) \). Plugging \( 9x - 6 \) into \( g(x) = \frac{x+6}{9} \): \[ g(f(x)) = g(9x - 6) = \frac{(9x - 6) + 6}{9} = \frac{9x}{9} = x. \] So, \( (g \circ f)(x) = x \). Now, let's put on our math hats for the final parts: c. \( (f \circ g)(5) = 5 \) (since you already found \( f \circ g \) is simply \( x \)). d. \( (g \circ f)(5) = 5 \) as well! There you have it, a mathematical journey that leads us back to where we started, right at \( x = 5 \)! 😊